Citizen participation in food systems policy making: A case study of a citizens' assembly [version 1; peer review: 2 approved] - Chris West; Bob Doherty; Yaadwinder Sidhu; Jane Gulec; Patricia Prado; Tony Heron; Alice Seaton; Paulina Flores Martinez (Emerald Publishing, 2020)
In this article, we offer a contribution to the emerging debate on the role of citizen participation in food system policy making. A key driver is a recognition that solutions to complex challenges in the food system need the active participation of citizens to drive positive change. To achieve this, it is crucial to give citizens the agency in processes of designing policy interventions. This requires authentic and reflective engagement with citizens who are affected by collective decisions. One such participatory approach is citizen assemblies, which have been used to deliberate a number of key issues, including climate change by the UK Parliament's House of Commons (House of Commons., 2019). Here, we have undertaken analysis of a citizen food assembly organized in the City of York (United Kingdom). This assembly was a way of hearing about a range of local food initiatives in Yorkshire, whose aim is to both relocalise food supply and production, and tackle food waste. These innovative community-based business models, known as 'food hubs', are increasing the diversity of food supply, particularly in disadvantaged communities. Among other things, the assembly found that the process of design and sortation of the assembly is aided by the involvement of local stakeholders in the planning of the assembly. It also identified the potential for public procurement at the city level, to drive a more sustainable sourcing of food provision in the region. Furthermore, this citizen assembly has resulted in a galvanizing of individual agency with participants proactively seeking opportunities to create prosocial and environmental change in the food system.